Koneksi Pusat dan Pinggiran: Perbandingan Teks Primbon Palinḍon Kraton Yogyakarta dan Palilinḍon Merapi-Merbabu - Ghis Nggar Dwiadmojo (Jumantara: Jurnal Manuskrip Nusantara, 2020)
The aims of this research are (1) to inventory and classify the corpus of the Javanese palilinḍon text and (2) to compare the palilinḍon text of Merapi Merbabu with the Primbon Palinḍon Kraton Yogyakarta text. The primary data of this study are the text of Palilinḍon, 29 L 328 (copied at Merapi Merbabu) and the text of Sĕrat Primbon Palintangan Palinḍon Pakĕdutan Add 12311 (copied at Yogyakarta Palace). The secondary data of this study are a cataloges containing information about manuscripts stored in libraries and museums in Indonesia and abroad. This research method is modern philology. There are 13 texts containing Javanese texts about palilinḍon. The 13 texts can be classified into two groups, the first copied at Merapi Merbabu and the second copied outside the Merapi Merbabu environment. Each group was taken one, namely Palilinḍon 29 L 328 which was copied at Merapi Merbabu and Primbon Palintangan Palinḍon Pakĕdutan Add 12311 which was copied in Yogyakarta Palace to be compared. Broadly speaking, the contents of the two texts are the same, namely containing information about events that followed the earthquake that occurred on the 12th month of Java. This proves the two texts are very strong connected. In the limited context of the Palilinḍon text, the connection of both of texts indicates the connection of both of scriptorium. Even though there are differences in word choices in the both of texts. In the text Palilinḍon 29 L 328 it is stated that if an earthquake occurs in a particular month, disaster will happen to the nagara while in the Primbon Palinḍon text Add 12311 it is stated that if an earthquake occurs in a particular month, the disaster will strike the desa. Nagara refers to the center, while the desa refers to the periphery. Nagara is the central representation, the residence of nobles and officials, if the negara is damaged the palace is also damaged. In the court's view this should not happen, then in Primbon Palinḍon Add 12311 the word 'nagara' was removed and the word ‘desa' was added as an object of disaster sufferers.